2017
DOI: 10.1111/1346-8138.13723
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4‐related disease and its skin manifestations

Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a systemic inflammatory condition characterized by tissue infiltration with IgG4 + plasma cells and an elevated serum IgG4 level. It usually occurs in middle-aged or older patients, with male predominance, and can involve multiple organs synchronously or metachronously. Patients with IgG4-RD generally respond to steroid therapy. IgG4-related skin lesions are typically erythematous and itchy plaques, subcutaneous nodules, or papules like prurigo nodularis located o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…It is also worth noting that high IgE-t levels have been reported in IgG4-related cutaneous pseudolymphoma, which has many features that resemble pcMZL. 51 In summary, we found that patients with SS and pcMZL, but not plaque phase MF, have high levels of SSAg-IgE and IgE-t. These results indicate that a pathogenic link may exist between an atopic diathesis and development of SS and possibly pcMZL.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It is also worth noting that high IgE-t levels have been reported in IgG4-related cutaneous pseudolymphoma, which has many features that resemble pcMZL. 51 In summary, we found that patients with SS and pcMZL, but not plaque phase MF, have high levels of SSAg-IgE and IgE-t. These results indicate that a pathogenic link may exist between an atopic diathesis and development of SS and possibly pcMZL.…”
Section: Discussionmentioning
confidence: 58%
“…An atopic diathesis may be another factor because three of seven (43%) of our patients with pcMZL had evidence of atopy with a positive Phadiatop screening test for aeroallergen‐specific IgE versus no patient with pcFCL. It is also worth noting that high IgE‐t levels have been reported in IgG4‐related cutaneous pseudolymphoma, which has many features that resemble pcMZL …”
Section: Discussionmentioning
confidence: 98%
“…IgG4related skin lesions are reportedly typically erythematous and itchy plaques, subcutaneous nodules, or papules like prurigo nodularis. Cutaneous lesions are predominantly located on the head and neck (12,13). Many patients with IgG4-related skin symptoms are reported to be Asian middle-aged and older men.…”
Section: Discussionmentioning
confidence: 99%
“…Given that any organ or tissue may be affected -bile ducts, pancreas as well as lacrimal and salivary glands in particular -, the condition is believed to be a multisystem disease [4]. Cutaneous manifestations in the form of erythematous plaques or subcutaneous nodules, predominantly arising on the face and neck, have been reported in up to 6.4 % of patients [5,6].…”
Section: Discussionmentioning
confidence: 99%